PENGARUH METODE PERMAINAN TRADISIONAL ENGKLEK TERHADAP PENINGKATAN BERHITUNG ANAK USIA 5-6 TAHUN DI TK BINA KREATIF SIPOHOLON - Purba, Susi (PRODI PKAUD, IAKN TARUTUNG, 2022)
Abstract This study aims to determine how big the effect of increasing numeracy skills in children after doing the traditional engklek game method on children aged 5-6 years at TK Bina Kreatif Sipoholon, This study uses an experimental approach, with a population of all children in TK Bina Kreatif Sipoholon totaling 30 people with a sample of 30 people. Data were collected using a closed questionnaire of 30 items compiled by the author based on variable indicators according to expert theory. Questionnaire trials were conducted on 30 children aged 5-6 years outside the research sample, and their validity and reliability were tested. The results of data analysis showed that there was a positive and significant effect on increasing numeracy skills in children after using the traditional engklek game method for children aged 5-6 years at TK Bina Kreatif Sipoholon with a coefficient of determination (r2) = 17.90% and tested for the normality of the X variable. median 49.2 mean = 50.9 mode 49.251, and Y variable normality test mean = 40.2 mode = 31.5 median = 36. rcount > rtable 0.424 > 0.361 t-test > ttable 2.476 > 2.048, Y regression test = 11.56 + 0.562 Keywords: Game Method, Counting Skills, Engklek Game